Structural And Magnetic Properties Of Spinel Mg-Ni Ferrites Nanoparticles Synthesized By Microwave Combustion Method - et. al., P. Antony Lyla , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Magnesium (Mg2+) ions doped nickel ferrite (NiFe2O4) nanoparticles with the general formula MgxNi1-xFe2O4 (y = 0.0 and 0.5) was synthesized by microwave combustion method, using urea as the fuel. Phase identification and structural parameters were analyzed by X-ray powder diffraction (XRD). Mg2+ doping concentration in NiFe2O4 greatly affected the size of the crystallite and obtained the size ranges from 22.5nm - 24.8 nm and all the samples show a single cubic spinal structure without any secondary step. For increased the concentration of Mg2+ doping, the lattice parameters are decreased, while decreasing trend has been observed in the case of particle size, which was confirmed by HR-SEM analysis. The influence of non-magnetic nature of Mg2+ doping on NiFe2O4 and replaces the magnetic nature of Ni2+ ions, which changes their magnetic properties and were studied under the applied field 15 kOe. The overall results showed that even a small amount of Mg2+ doping changes the structural and magnetic properties of the spinel NiFe2O4 nanoparticles.